Use of Bacteroidales Microbial Source Tracking To Monitor Fecal Contamination in Fresh Produce Production - Ravaliya, Kruti (American Society for Microbiology, 2014)
In recent decades, fresh and minimally processed produce items have been associated with an increasing proportion of food-borne illnesses. Most pathogens associated with fresh produce are enteric (fecal) in origin, and contamination can occur anywhere along the farm-to-fork chain. Microbial source tracking (MST) is a tool developed in the environmental microbiology field to identify and quantify the dominant source(s) of fecal contamination. This study investigated the utility of an MST method based on Bacteroidales 16S rRNA gene sequences as a means of identifying potential fecal contamination, and its source, in the fresh produce production environment. The method was applied to rinses of fresh produce, source and irrigation waters, and harvester hand rinses collected over the course of 1 year from nine farms (growing tomatoes, jalapeño peppers, and cantaloupe) in Northern Mexico. Of 174 samples, 39% were positive for a universal Bacteroidales marker (AllBac), including 66% of samples from cantaloupe farms (3.6 log(10) genome equivalence copies [GEC]/100 ml), 31% of samples from tomato farms (1.7 log(10) GEC/100 ml), and 18% of samples from jalapeño farms (1.5 log(10) GEC/100 ml). Of 68 AllBac-positive samples, 46% were positive for one of three human-specific markers, and none were positive for a bovine-specific marker. There was no statistically significant correlation between Bacteroidales and generic Escherichia coli across all samples. This study provides evidence that Bacteroidales markers may serve as alternative indicators for fecal contamination in fresh produce production, allowing for determination of both general contamination and that derived from the human host.